Dana Sukuk sebagai Alternative Sumber Dana Pembiayaan pada Bank Syariah - Yusuf Wildan Nasution; Marliyah Marliyah; Khairina Tambunan (Economic Reviews Journal, 2023)
This study looks at the issuance and development of sukuk at Bank CIMB NIAGA Syariah and looks at the utilization of sukuk funds at Bank Cimb Niaga CIMB NIAGA Syariah. The method in this research uses descriptive qualitative, in data collection using documentation techniques with secondary data as the analysis. The purpose of this research is to determine the process of issuance and development of sukuk funds at Bank CIMB NIAGA Syariah and to determine the utilization of sukuk funds at Bank CIMB Niaga Syariah. The function of this research is to be able to increase scientific literature in the field of Islamic capital markets related to Islamic banking, related to Sharia Bank Sukuk. The result of this research is that in the issuance of Sukuk Mudharabah Bank CIMB NIAGA Syariah has followed the POJK rules, which have been explained in several articles related to the issuance of Sukuk Mudharabah. And there is conformity in the Sukuk Mudharabah issuance scheme according to the OJK with the CIMB NIAGA Syariah Bank Sukuk Mudharabah scheme. As for the development of sukuk funds at Bank CIMB NIAGA Syariah, it has been running according to the target in their issuance and it can be said that the bank with the highest value of sukuk registered with the Indonesian Financial Services Authority is Bank CIMB NIAGA Syariah. In utilizing sukuk funds at Bank CIMB NIAGA Syariah, use them to support sharia financing with a musyarakah mutanaqisah (MMQ) financing contract   Keywords: Fund Utilization, Sukuk Mudharabah, Sharia Financing Musyarakah Mutanaqisah